Investigation on routing aspects towards RPL optimization - Wan Abdul Rahman, Wan Fariza; Islam, Md Rafiqul; Hassan Abdalla Hashim, Aisha (Asian Research Publishing Network (ARPN), 2015)
Routing in Low-power and Lossy Networks (LLNs) requires low overhead on data packets, low routing overhead, minimal memory and computation requirements, and support for sleeping nodes considering battery saving. Most of the devices are distinguished by their low bandwidth, short range, scarce memory capacity, limited processing capability and other attributes of inexpensive hardware. These devices are designed to be compatible with the IEEE 802.15.4 standard. IPv6 over IEEE 802.15.4 has been defined to carry IPv6 packets over IEEE 802.15.4 and similar networks, due to its capability to support routing over possibly various types of interconnected links. The IETF Routing Over Low Power and Lossy Networks (ROLL) working group has designed the IPv6 route-over Routing Protocol for LLNs, known as RPL, which covers the routing requirements of all application domains. However, there are still a number of routing aspects to be tackled in RPL, including memory efficiency, routing overhead and loops occurrence. Therefore, the purpose of this paper is to highlight these issues and investigate the efforts/approaches for solving them.